2021
DOI: 10.1038/s42003-021-02065-6
|View full text |Cite
|
Sign up to set email alerts
|

Computationally guided in-vitro vascular growth model reveals causal link between flow oscillations and disorganized neotissue

Abstract: Disturbed shear stress is thought to be the driving factor of neointimal hyperplasia in blood vessels and grafts, for example in hemodialysis conduits. Despite the common occurrence of neointimal hyperplasia, however, the mechanistic role of shear stress is unclear. This is especially problematic in the context of in situ scaffold-guided vascular regeneration, a process strongly driven by the scaffold mechanical environment. To address this issue, we herein introduce an integrated numerical-experimental approa… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 45 publications
(63 reference statements)
0
4
0
Order By: Relevance
“…Another intrinsic property of a woven TEVG is a wavy luminal surface. Flow oscillations and WSS are well-known for influencing cell behavior and in vivo remodeling [48,49]. In particular, low shear stress zones have been correlated with the development of intimal hyperplasia [50,51].…”
Section: Discussionmentioning
confidence: 99%
“…Another intrinsic property of a woven TEVG is a wavy luminal surface. Flow oscillations and WSS are well-known for influencing cell behavior and in vivo remodeling [48,49]. In particular, low shear stress zones have been correlated with the development of intimal hyperplasia [50,51].…”
Section: Discussionmentioning
confidence: 99%
“…S1 ). The completed medium was used as the perfusion medium which was mixed with 0.7 mg/ml Xanthan gum (Sigma-Aldrich) to increase the viscosity [ 19 , 33 ], and the medium was refreshed every day.…”
Section: Methodsmentioning
confidence: 99%
“…Conversely, disturbed flow with oscillatory and low WSS, is a pathological flow pattern, resulting in ECs loosing parallel alignment and elongation, and remodeling of cell-junctions. Contrary to laminar flow conditions, KLF2 expression is downregulated while inflammatory factors are upregulated in disturbed flow areas [ [17] , [18] , [19] , [20] ]. In addition, studies have shown that high RRT and OSI can predict a spectrum of pathological alterations and their occurrence in a disturbed flow area [ 9 ].…”
Section: Introductionmentioning
confidence: 99%
“…Hemodynamic metrics were defined to quantify disturbed flow and disturbed WSS in the anastomotic region. Although multiple hypotheses regarding the definition of disturbed WSS exist [ 27 ], here it was assumed that WSS outside the physiological range (0.1–7 Pa [ 28 ]), WSS sufficiently high to cause irreversible endothelial damage (>40 Pa [ 29 ]) and highly oscillatory WSS [ 30 ] were detrimental to graft longevity. Disturbed flow and non-physiological WSS were assessed over the total venous segment and in the venous perianastomotic region of all simulations.…”
Section: Methodsmentioning
confidence: 99%